Alcohol prohibition and pricing at the pump - Kai Fischer (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2022)
Firms often sell a transparent base product and a valuable add-on product. If only some consumers are aware of the latter, the add-on's effect on the base product's price will be ambiguous. Cross-subsidization between products to bait uninformed consumers might lower, intrinsic utility from the add-on for informed consumers might raise the price. We study this trade-off in the gasoline market by exploiting an alcohol sales prohibition at stations as an exogenous shifter of add-on availability. Gasoline margins drop by 5% during the prohibition. The effect is mediated by shop variety and local competition. Implications for gasoline market definition arise.
Keywords: L11; L91; R41; 330; Off-Premise Alcohol Prohibition; Gasoline Market; Multi-Product Firms